Mathematical Analysis Of A Modular Network Coordinating The Cell Cycle And Apoptosis - Gheorghe Craciun; Baltazar Aguda; Avner Friedman (Mathematical Biosciences and Engineering)
The cell-division cycle and apoptosis are key cellular processes deregulated during carcinogenesis. Recent work of Aguda and Algar suggests a modular organization of regulatory molecular pathways linking the cellular processes of division and apoptosis. We carry out a detailed mathematical analysis of the Aguda-Algar model to unravel the dynamics implicit in the model structure. In addition, we further explore model parameters that control the bifurcations corresponding to the aforementioned cellular state transitions. We show that this simple model predicts interesting behavior, such as hysteretic oscillations and different conditions in which apoptosis is triggered.